2014
DOI: 10.3109/15622975.2013.866693
|View full text |Cite
|
Sign up to set email alerts
|

The Tutsi genocide and transgenerational transmission of maternal stress: epigenetics and biology of the HPA axis

Abstract: PTSD was associated with NR3C1 epigenetic modifications that were similarly found in the mothers and their offspring, modifications that may underlie the possible transmission of biological alterations of the HPA axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
182
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(192 citation statements)
references
References 38 publications
5
182
1
4
Order By: Relevance
“…Women's experience of intimate partner violence during pregnancy also has been associated with increased NR3C1 methylation in their adolescent offspring (52). When women were exposed to the Tutsi genocide during pregnancy, their children had higher methylation of the NR3C1 exon 1F than offspring from nonexposed women (53). NR3C1 is not the only locus where DNA methylation is modified by maternal stress.…”
Section: Discussionmentioning
confidence: 99%
“…Women's experience of intimate partner violence during pregnancy also has been associated with increased NR3C1 methylation in their adolescent offspring (52). When women were exposed to the Tutsi genocide during pregnancy, their children had higher methylation of the NR3C1 exon 1F than offspring from nonexposed women (53). NR3C1 is not the only locus where DNA methylation is modified by maternal stress.…”
Section: Discussionmentioning
confidence: 99%
“…Perroud et al similarly found hypermethylation of the NR3C1 promoter in offspring born to Tutsi widows pregnant during the genocide of ethnic Tutsis in Rwanda (Perroud et al, 2014). However, another study has reported that there is a nonsignificant effect of perinatal stress, defined as the sum of maternal psychological problems during pregnancy or the 3 months after delivery, on NR3C1 methylation in adolescent offspring (van der Knaap et al, 2014).…”
Section: Epigeneticsmentioning
confidence: 99%
“…Moreover, exposed mothers and their children had higher methylation of the NR3C1 exon 1F than nonexposed groups and exposed mothers showed higher methylation of CpGs located within the NR3C2 coding sequence than nonexposed mothers (Perroud et al. 2014). Therefore, this research emphasized that transgenerational impact of a trauma is a reality not only from a clinical point of view but also from a biological one.…”
Section: Genetic Services In Rwandamentioning
confidence: 99%